High performance city rendering in Vulkan - Zhang, Alex (2019)
City scale scenes often contain large amounts of geometry and texture that cannot altogether fit on GPU memory. Our ongoing work seek to minimise texture memory usage by streaming only view-relevant textures and to improve rendering performance using parallel opportunities offered by Vulkan, the latest generation of graphics API. Our result presents a high performance rendering of a city with streaming textures after CPU and GPU culling.